Biofacies Analysis of the Cabo Frio Coast, Rio de Janeiro, Based in Benthic Foraminifera - Guedes, Daniel Coré; Vilela, Claudia Gutterres; Baptista Neto, José Antonio; Macedo, Mariana Cardoso; Santiago, Neyva de Lima; Bruno, Regina Lucia Machado (Anuário do Instituto de Geociências, 2017)
In July 2009, samples from the sediment-water interface were collected on the Cabo Frio - RJ inner shelf, in front of the Peró Beach, in order to characterize environmentally this area through the study of benthic foraminifera. The study area lies between the latitudes 22ºS and 23ºS, and the longitudes 41ºW and 42ºW and presents water depths ranging from 10m to 30 m. In the laboratory the samples were washed, dried in an oven, splitted and taxonomically classified. Thirty-seven samples were analyzed and almost all specimens were identified in species. The samples with higher abundance, richness and diversity were found in deeper regions far away from the coast, containing more than 5000 individuals. Three abundant samples were found in the south entrance, near the Ponta do Peró. The presence of abundant broken specimens was observed, indicating the current dynamics in the region. Overall the species Poroeponides lateralis and Eponides repandus, typical from the shelf, and Bulimina marginata, typical species of proximal environments, appeared as dominant (present with a percentage of 10% or more). Quinqueloculina agglutinans and Textularia agglutinans were considered principal species in seven samples (present with a percentage of 5% or more). The presence of Buccella peruviana characterizes the influence of the currents from the south of Brazil in the Cabo Frio shelf. Ten barren samples were found, most of them located in shallower regions. Although the samples are located in the inner shelf and at low depth, 30% of the samples had high abundance and diversity, probably by the upwelling effects which occur in the region. Three biofacies were identified. Two of them were characterized by changes from a proximal environment to a shelf environment and, in one of these two, the abundance of Buccella peruviana was observed. The other biofacies presented broken specimens in abundance.